Réponses

2014-05-30T11:39:41+02:00
2x + 6 = 5x - 9
2x + 6 - 2x = 5x - 9 - 2x
6 = 3x - 9
6 + 9 = 3x - 9 +9
 \frac{15}{3}  =  \frac{3x}{3}
5 = x

29 - 3X = 2X -1
29 - 3x +1 = 2x -1 + 1
30 - 3x = 2x
30 - 3x + 3x = 2x +3x
 \frac{30}{5} =  \frac{5x}{5}
6 = x

2x + 5 = 5 - 2x
2x + 5 + 2x = 5 - 2x + 2x
4x + 5 = 5
4x + 5 - 5 = 5 -5
 \frac{4x}{4}  \frac{0}{4}
x = 0

3x - 12 = 9x - 27
3x - 12 + 27 = 9x - 27 + 27
3x + 15 = 9x
3x + 15 - 3x = 9x - 3x
 \frac{15}{3}  \frac{3x}{3}
5 = x

3x - 8 = x + 10
3x - 8 - x = x + 10 - x
2x - 8 = 10
2x - 8 +8 = 10 + 8
 \frac{2x}{2} =  \frac{18}{2}
x = 9